2002
DOI: 10.1089/10430340252939023
|View full text |Cite
|
Sign up to set email alerts
|

A Single Short Stretch of Homology Between Adenoviral Vector and Packaging Cell Line Can Give Rise to Cytopathic Effect-Inducing, Helper-Dependent E1-Positive Particles

Abstract: An undesirable byproduct from recombinant adenoviral vectors is the emergence of replication competent adenovirus (RCA) that result from rare homologous recombination events between the viral E1-containing (permissive) mammalian host cell genome and the virus itself, restoring the E1 gene to the viral genome. To reduce or eliminate the problem of RCA, we evaluated production of a first generation Ad5 vector (Ad5FGF4) in the cell line PER.C6. This E1-transformed human cell line contains only Ad5 nucleotides 459… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Many recombinant Ad batches have been produced using the PER.C6 cell line, and RCA have not been detected. We have previously demonstrated the importance of using the appropriate vector-plasmid system in combination with PER.C6 cells, showing that a 177-bp sequence homology at one end of the E1 region is sufficient for recombination between cells and vector (14). In that study we showed that the single crossover event observed gave rise to a helper-dependent, replication-incompetent virus with a low frequency (less than 1 in 10 11 particles).…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Many recombinant Ad batches have been produced using the PER.C6 cell line, and RCA have not been detected. We have previously demonstrated the importance of using the appropriate vector-plasmid system in combination with PER.C6 cells, showing that a 177-bp sequence homology at one end of the E1 region is sufficient for recombination between cells and vector (14). In that study we showed that the single crossover event observed gave rise to a helper-dependent, replication-incompetent virus with a low frequency (less than 1 in 10 11 particles).…”
mentioning
confidence: 85%
“…This DNA was cotransfected with PacI-digested cosmid pWE/ AdAfIII-rITR (6) into PER.C6 cells (3) using Lipofectamine and the protocol provided by the manufacturer (Life Technologies). Virus propagation and purification have been described previously (14). For each production lot, a separate aliquot from a master virus bank was used for the initial infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wild-type virus may contaminate vector preparations, and RCV may be formed during production due to recombination between the vector and the helper sequences found in complementary cell lines or plasmids (Escarpe et al, 2003;Murakami et al, 2002;Nony et al, 2003;Sastry et al, 2005) The presence of wild-type virus or RCV may affect vector expression and mobilization.…”
Section: Assay For Replication Competent Vector (Rcv)mentioning
confidence: 99%